2003
DOI: 10.1093/jhered/esg087
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure, Mating System, and Long-Distance Gene Flow in Heart of Palm (Euterpe edulis Mart.)

Abstract: We report a detailed analysis of the population genetic structure, mating system, and gene flow of heart of palm (Euterpe edulis Mart.-Arecaceae) in central Brazil. This palm is considered a keystone species because it supplies fruits for birds and rodents all year and is intensively harvested for culinary purposes. Two populations of this palm tree were examined, using 18 microsatellite loci. The species displays a predominantly outcrossed mating system (tm = 0.94), with a probability of full sibship greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
93
4
46

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(163 citation statements)
references
References 29 publications
20
93
4
46
Order By: Relevance
“…In contrast, studying two populations of the Atlantic Forest palm Euterpe edulis, GAIOTTO et al (2003) found an average H e over 18 microsatellite loci of 0.86, a result higher than that found in the current study. O. phalerata has high genetic diversity which is likely due to a high outcrossing rate combined with the occurrence of protogyny, extensive pollen flow among populations via beetles and wind (ANDERSON and BALICK, 1988), as well as the high density of palms per hectare (on average 453.3 trees ha -1 ).…”
Section: Genetic Diversitycontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, studying two populations of the Atlantic Forest palm Euterpe edulis, GAIOTTO et al (2003) found an average H e over 18 microsatellite loci of 0.86, a result higher than that found in the current study. O. phalerata has high genetic diversity which is likely due to a high outcrossing rate combined with the occurrence of protogyny, extensive pollen flow among populations via beetles and wind (ANDERSON and BALICK, 1988), as well as the high density of palms per hectare (on average 453.3 trees ha -1 ).…”
Section: Genetic Diversitycontrasting
confidence: 99%
“…Selection between seed, seedling, and juvenile to adult stage in tree species is well documented. For example, in Astrocaryum mexicanum (EGUIARTE et al, 1992), E. edulis (GAIOTTO et al, 2003), and Copaifera langsdorffii (SEBBENN et al, 2011), higher levels of inbreeding were found in seeds and juveniles than in adults.…”
Section: Genetic Diversitymentioning
confidence: 99%
“…The pollen immigration from outside the sampled farm may represent a contribution of pollen and seeds for 63.16% of seedlings sampled, suggesting long distance gene flow of pollen and/or seeds. The observed long distance pollen dispersal found in this study agrees with the observations in other species of tropical trees of low population density, thereby suggesting that the average distance of pollen dispersal is generally greater than 200 m (Nason and Hamrick, 1997;White et al, 2002;Gaiotto et al, 2003;Dick et al, 2003;Carneiro et al, 2007;Cloutier et al, 2007;Eduardo et al, 2008). The agroforestry system to which the population of C. legalis is found most likely favors the action of pollen and seed dispersers.…”
Section: Discussionsupporting
confidence: 88%
“…A magnitude da correlação entre o PIC e o número de alelos também foi alta e significativa (r=0,78, P 0,04), existindo uma relação direta entre eles, ou seja, quanto maior no número de alelos, maior será o valor do PIC. Elevados níveis de polimorfismos também foram detectados por Gaiotto et al (2003) e Conte et al (2006) ao utilizarem os mesmos primers em populações de palmiteiro (Euterpe edulis). Germoplasma de outras palmeiras também apresentam alta diversidade quando analisados com marcadores microssatélites (Perera et al, 2000(Perera et al, , 2001Meerow et al, 2003;Zehdi et al, 2004a,b).…”
Section: Resultsunclassified